PENINGKATAN KREATIVITAS SISWA DALAM PEMBELAJARAN SENI TARI DENGAN MENERAPKAN MODEL COOPERATIVE LEARNING DI SMP NEGERI 1 PADANG PANJANG - Dian Trisna Mustika; Yuliasma Yuliasma; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2013)
Abstract The research aimed at understanding and describing the implementation of cooperative learning model in improving student’s creativity in the learning dancing at SMP Negeri 1 Padang Panjang. The problem in the learning dacing at SMP Negeri 1 Padang Panjang was the student were lack of creativity. The object of the research was grade VIII.E students of SMP Negeri 1 Padang Panjang. The research showed that the implementation of cooperative learning model could improve students’ creativity in learning dancing. It was seen from their creativity test. On the cycle 1, their average score was 51.5 while on the second cycle it was improved up to 81.5. Thus, the implementation of cooperative learning model could improve students; creativity in learning dancing at SMP Negeri 1 Padang Panjang. Kata kunci : hasil belajar, Model Cooperative Learning